Filosofía zombi - Aldegani, Emilliano (Prometeica - Revista de Filosofía y Ciencias, 2012)
FERNÁNDEZ GONZALO, Jorge. Filosofía zombi. Primeraedición. Barcelona. Anagrama. 2011. ISBN: 978-84-339-6325-3.-